Theatre and emergency services rendered by generalist medical practitioners in district hospitals in the Western Cape - M.R. de Villiers; P.J.T. de Villiers (South African Family Practice)
District hospitals play an important role in the rendering comprehensive health services to communities. The district hospital is an integral part of the district health system providing not only level-one hospital services but also outreach and support to primary health care services. District hospitals are staffed by generalist medical practitioners who are required to perform a wide range of clinical duties and procedures. A situation analysis to identify the range of duties performed by medical practitioners in rendering emergency and theatre services at the district hospital in the Western Cape was conducted in 2001. Data was collected from the casualty register, theatre register, routine monthly report, a medical officer questionnaire and a questionnaire collecting general information about all the district hospitals in the Western Cape Province.